Development of a Game Based Learning (GBL) Model Assisted by Escape Room to Improve Conceptual Understanding and Self-Efficacy - Farah Nafiisafitry; Istiyono, Edi (Department of Physics Education, Universitas Mataram, 2025)
The purposes of this study were to (1) describe the design of the GBL model assisted by an Escape Room that was developed to improve students’ conceptual understanding and self-efficacy, (2) produce a high-quality GBL model assisted by an Escape Room that is suitable for use in terms of content validity, construct validity, and model coherence, (3) identify students’ profiles regarding the GBL model assisted by an Escape Room based on the results of limited implementation and user feedback, (4) determine the implementation quality of the GBL model assisted by an Escape Room in physics learning, and (5) examine the effectiveness of the GBL model assisted by an Escape Room in improving students’ conceptual understanding and self-efficacy. The study was conducted at a senior high school in Purbalingga with one experimental class and two comparison classes. The research model employed was the 4D model. The instruments used included tests, questionnaires, and observation sheets. The analysis techniques consisted of Sbi, Aiken’s V to measure content validity, empirical validity using Rasch model analysis with INFIT MNSQ values ranging from 0.7 to 1.3, along with normality tests, homogeneity tests, MANOVA, and one-way ANOVA to determine differences in the impact of the product intervention. The findings showed that (1) the characteristics of the developed model, from the learning syntax to the media produced, created meaningful and memorable learning experiences, (2) the GBL model assisted by an Escape Room fell into the appropriate category, (3) there was an improvement in learning outcomes and differences in treatment between classes, with the experimental class achieving the highest results, (4) the model was proven to be practical with full implementation in the classroom, and (5) the GBL model assisted by an Escape Room was effective, as indicated by the effect sizes for conceptual understanding and self-efficacy, which were 0.380 and 0.427 respectively. This model demonstrates strong potential for use in challenge-based or gamified thematic learning in classroom settings.